PENGARUH MODEL PEMBELAJARAN INQUIRY TRAINING TERHADAP KETERAMPILAN PROSES SAINS PADA PEMBELAJARAN FISIKA - Muliati, Sri; Bukit, Nurdin (Universitas Negeri Medan, 2016)
This Research was aimed to know the effect of inquiry training model on science process skill of student. This research is quasy experiment research. The sample of this research that was taken by using cluster random sampling. Based on the research it can that the effect of inquiry training learning model significantly give a better on science process skill of students and more understand the indicators on each component of the science process skill the average 88,57 and a deviation standard of 7.